Longitudinal Association of Handgrip Strength with Medical Use and the Risk of Hospitalization in Korean Adults - Junghoon Kim (Asian Society of Kinesiology, 2021)
OBJECTIVES Age-related loss of muscular strength may contribute to medical health condition. Decreased handgrip strength is associated with an increased risk of chronic diseases, disability, and mortality. However, it is not known whether handgrip strength is also linked with hospitalization and medical use from the long-term cohort study in middle-aged adults. Thus, we aimed to investigate the association of handgrip strength levels, medical use, and hospitalization in Korean adults. METHODS This large prospective study was based on data from Korean Longitudinal Study of Ageing 2006 to 2018. In total, 9,228 participants aged ≥45 years were included for this study. Handgrip strength was measured using dynamometer, and classified into quartiles by sex-specific cutoff point. RESULTS Significantly higher hazard ratio (HR) for hospitalization was observed in lower handgrip strength (HR: 1.22, 95% CI:1.11-1.34) compared to higher handgrip strength (reference) in the fully adjusted model. We also found longitudinal association of handgrip strength levels and the use of hospitalization and outpatient medical care during 12 years following period using mixed effect modes with time-dependent interaction. CONCLUSIONS Our results suggests that lower handgrip strength was associated with increased the risk of hospitalization and use of medical care in Korean population. This study highlights the maintaining of muscular strength may play an important role in the reduction of risk for hospitalization and medical use by preventing chronic diseases.